TINGKAT KEPATUHAN DISIPLIN PNS OLEH PEGAWAI NEGERI SIPIL DI LINGKUNGAN KABUPATEN PEMALANG - Kumala, Mentari Berliana; Aulia, Mila Rizki; Adiyatma, Septhian Eka (Indonesian State Law Review (ISLRev), 2021)
Civil Servants, which were later abbreviated as PNS in Law (N0).5 of 2014 concerning State Civil Apparatus, are tasked with providing services to the community in their bureaucratic structure towards a good governance structure. PNS according to Government Regulation No. 53 of 2010 which regulates the discipline of civil servants is made with the aim of taking disciplinary action for the bureaucracy so that it can carry out its duties and obligations to the community with good work procedures. This study will examine how the implementation of civil servant discipline in the Pemalang Regency environment and how to overcome the obstacles found in its implementation. The purpose of this study was to determine the implementation of Government Regulation No. 53 of 2010 and the awareness of civil servants in responding to the rules that apply in Pemalang Regency. This research method uses sociological juridical, with analytical descriptive which will produce primary and secondary data related to the application of civil servant discipline, the analytical method used is qualitative analysis which will produce in-depth research in order to find out the problems that arise and can provide existing solutions.